Analysis Of Satirical Language Style In Poetry Collection Malu (Aku) Jadi Orang Indonesia By Taufiq Ismail And Implications For Indonesian Language Learning In High School - Mahajani, Tri; Chodijah, Siti; Ekowati, Ainiyah; Islami, Enur Mutiah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Language style is a way of expressing thoughts or feelings through language used specifically to show one's soul and personality. One of the language styles that can be used in literary works is the satirical language style. Satirical language style is a language style that expresses an intention with language that is satirical and has a strong purpose regarding the meaning or impression of the sentence. This study examines the satirical language style in poetry collection Malu (Aku) Jadi Orang Indonesia by Taufiq Ismail and its implications for Indonesian language learning in high school. The focus of the problem in this study is the use of satirical language style in poetry collection Malu (Aku) so the Indonesian Taufiq Ismail works as many as 10 poems and implications of satirical language style in poetry collection Malu (Aku) so the Indonesian Taufiq Ismail works on learning Indonesian in high school. This study aims to describe the use of satirical language style in poetry collection Malu (Aku) Jadi Orang Indonesia by Taufiq Ismail with descriptive qualitative research methods. The results of the analysis of research that has been done there are 40 data, consisting of 9 types of satire irony, 22 types of satire cynicism, and 9 types of sarcasm satire. A collection of poems Malu (Aku) Jadi Orang Indonesia by Taufiq Ismail containing satirical language can be implemented in Indonesian language learning in high school.